The implementation of the hermeneutic-dialectic methodology for an ABET needs assessment in a rural area of the Northern Province - Rakoma, Maletsepe Monica (2012)
M.Ed. === A number of studies has shown that adult education is a matter of great concern in South Africa, and the Northern Province has been earmarked as one of the regions with which needs thorough redressing and restitution of equality. This is because this region is constituted of rural areas characterised by poverty, unemployment and lack of proper housing and infrastructure. Many adults, most of hem middle-aged, and teenagers are illiterate because they either missed out on school or dropped out of school. It therefore becomes important that, given the situation in the province, ABET centres and relevant programmes be established and provided in order to fight against illiteracy. The literature shows that good provision in adult education should go hand in hand with the identification and assessment of the needs of adult learners. Whatever investigation is made on the needs of adult learners, the social and cultural background of the learner should be considered because it is the context which guides and influences expression of their needs. This suggests that appropriate methods for conducting ABET needs assessment should be selected and used - methods which will adapt to the background of the adult learners. The aim of this study, therefore, is to describe the process of conducting a needs assessment for the development of a programme for adult learners using the hermeneutic-dialectic methodology, and simultaneously assessing the viability of this methodology for developing appropriate needs assessment instruments in rural areas of South Africa. This study was approached from a constructivist (interpretive) perspective. This perspective is one which asserts that there exists multiple realities which are socially constructed. Within this perspective, the hermeneutic-dialectic methodology is suggested as a way of conducting research. Using this methodology as a framework, the open interview method was used in order to elicit constructions of participants. It became evident that the hermeneutic-dialectic methodology may be one of the appropriate methodologies which can be used for conducting needs assessment in rural areas. This is because the methodology adapts to the social and cultural background of the adult learners.